- (4) / (w^2 + 7w - 18) = (4w) / (w+9)
Cross multiply to get:
-4(w+9) = (w^2+7w-18)4w
-4w-36 = 4w^3+28w^2 -72w
4w^3 +28w^2 -68w + 36 = 0
w^3 + 7w^2 - 17w +9 = 0
(w+9)(w-1)^2 = 0
W = 1,1, -9 (hole at x = -9)
2007-05-19 11:26:24
·
answer #1
·
answered by ironduke8159 7
·
0⤊
1⤋
I am not going to do it for you, but I will get you going:
Well, first factor (w^2 + 7w - 18). You will discover that (w+9) is a factor. Multiply both sides by (w+9), and the result is a quadratic equation which you can solve.
When you solve it, you should get w=1 as the only solution.
2007-05-19 11:28:34
·
answer #2
·
answered by MSDTT 2
·
0⤊
0⤋
- (4) / (w^2 + 7w - 18) = (4w) / (w+9)
frist we factor the trinomial w^2 + 7w - 18
which gives us:
- (4) / (w+9)(w-2) = (4w) / (w+9)
Since 1/ (w+9) is common in both sides, we factor it out by multiplying both sides by(w+9)
the equation becomes,
-4/ (w-2) = 4w
cross multiply...
4w^2 - 8w = -4
4w^2 - 8w + 4 = 0
w^2 - 2w + 1 = 0
(w-1)^2 = 0
therefore, w=1,1 OR 1 multiplicity 2
2007-05-19 14:17:50
·
answer #3
·
answered by Rach 2
·
0⤊
0⤋
Here is what I can see from just looking at it..
if you multiply both sides by denominators, i.e. cross multiply but don't multiply out...
instead, factor the quadratic term, you will see this..
-4(w+9) = 4w(w+9)(w-2)
now, bring right term to left side to get
-4(w+9) - 4w(w+9)(w-2)=0
you can see you can factor by groups..
to get -4(w+9)[ 1-w(w-2)] = 0
set left factor =0 to get w=-9
set 1-w^2-2w = 0 factor to get
(w-1)^2 = 0
which gives w=1.... so, sulutions are w=1, since we can't divide by zero, w=-9is not allowed. and only one solution survives..;)
2007-05-19 11:32:12
·
answer #4
·
answered by JAC 3
·
0⤊
0⤋
-4/(w+9)(w-2)=4w/w+9 factor
-4/(w+9)(w-2)=4w(w-2)/(w+9)(w-2) multiply 2nd equation
-4=(4w)(w-2) get rid of fractions
-4/4w=w-2 divide by 4w
-w=w-2 cancel 4
-2w=-2 divide by 2
w=1
i believe that is the right answer but i'm not 100% sure so check to make sure
2007-05-19 11:28:37
·
answer #5
·
answered by cincynattifanmp 1
·
0⤊
1⤋
h(x) = 4(x+3)^2 + 7 the reason of this could properly be a horizontal translation gets subtracted from x. A shift of -3 consequences interior the previous function on account that x -(-3) = x +3. A vertical shift gets subtracted from y. So, in case you had to shift it 3 gadgets up, it may appear as if this: h(x) - 3 = 4x^2 +7, and you may purely remedy for h(x) to yield h(x) = 4x^2 + 10.
2017-01-10 09:10:14
·
answer #6
·
answered by ? 4
·
0⤊
0⤋